Arabidopsis thaliana detoxification gene AtDTX1 is involved in trichothecene 3-acetyl-deoxynivalenol efflux - Guixia Hao; Jackson Edwards; Nicholas Rhoades; Nicholas Rhoades; Susan P. McCormick (Frontiers in Plant Science)
The fungal pathogen Fusarium graminearum causes Fusarium head blight (FHB) on wheat and produces trichothecene mycotoxins that contaminate grains. Deoxynivalenol (DON) and its acetylated derivatives, including 3-acetyl-DON (3-ADON) and 15-acetyl-DON (15-ADON), are the most common trichothecenes found in contaminated grains, which causes food and feed safety issues. Approaches that detoxify DON can reduce FHB and mycotoxin contamination. Our previous study showed that transgenic Arabidopsis thaliana expressing a F. graminearum 3-O-acetyltransferase self-protection enzyme (FgTri101), converted DON to 3-ADON and excreted 3-ADON out of plant cells to protect plant growth and development. The goal of the current study was to identify the transporter involved in 3-ADON excretion and utilize it to reduce toxicity and FHB. To identify trichothecene transporter candidates, transcriptomic studies were conducted on FgTri101 transgenic A. thaliana seedlings treated with DON (50 mg/L, 24 h) versus untreated controls. Transcriptomic analyses revealed that three transporter genes, including two A. thaliana detoxification genes (AtDTX1 and AtDTX3) and one ABC transporter (ABCB4), were upregulated by DON treatment. Atdtx1 mutant transported 3-ADON less efficiently than Atdtx3 and Atabcb4 mutants. Therefore, the A. thaliana Col-0 mutant Atdtx1 line was transformed and expressed FgTRI101. The Atdtx1 mutant lines expressing FgTRI101 showed resistance to DON but had significantly shorter roots than the FgTRI101 Col-0 transgenic line. Furthermore, significantly less 3-ADON was detected in the media used to grow the transgenic Atdtx1 mutant seedlings expressing FgTRI101 than the Col-0 seedlings expressing FgTRI101. These data indicate that AtDTX1 is involved in efflux of 3-ADON and that at least another transporter or other mechanism is associated with 3-ADON transport.